2019
DOI: 10.1111/bju.14733
|View full text |Cite
|
Sign up to set email alerts
|

Use of indocyanine green to minimise uretero‐enteric strictures after robotic radical cystectomy

Abstract: Objective To evaluate the impact of indocyanine green (ICG) for assessing ureteric vascularity on the rate of uretero‐enteric stricture formation after robot‐assisted radical cystectomy (RARC) with intracorporeal urinary diversion (ICUD). Patients and methods We identified 179 patients undergoing RARC and ICUD between January 2014 and May 2017, and divided the patients into two groups based on the utilisation of ICG for the assessment of ureteric vascularity (non‐ICG group and ICG group). We retrospectively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 21 publications
2
40
0
1
Order By: Relevance
“…The long-term incidence of UAS after ileal conduit diversion ranges widely, between 2-22% (14)(15)(16)(17). While the exact mechanisms of benign stricture formation are not known, it is thought to be predominantly due to ischaemia and subsequent scarring at the anastomosis (18). Although poor surgical technique and extensive ureteral mobilization could be major risk factors for UAS, it is evident that other factors may jeopardize the blood supply to the distal tract of the ureter, increasing the risk of stricture (3).…”
Section: Discussionmentioning
confidence: 99%
“…The long-term incidence of UAS after ileal conduit diversion ranges widely, between 2-22% (14)(15)(16)(17). While the exact mechanisms of benign stricture formation are not known, it is thought to be predominantly due to ischaemia and subsequent scarring at the anastomosis (18). Although poor surgical technique and extensive ureteral mobilization could be major risk factors for UAS, it is evident that other factors may jeopardize the blood supply to the distal tract of the ureter, increasing the risk of stricture (3).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the role of ICG technique to easily recognize tissue vascular perfusion was used to prevent ischemic ureteral complications, such as strictures. Ahmadi et al [34] reported a significant reduction in the per-patient rate of uretero-enteric anastomotic stricture from 10, 6% to 0% (p = 0.020).…”
Section: New Technologies In Robotic Surgery: State Of Art and Futurementioning
confidence: 97%
“…Robotic cystectomy improves perioperative outcomes while maintaining cancer control. [1][2][3] Currently, most of the controversy comes from deciding on the urinary diversion and reconstructive technique after RARC: extracorporeal urinary diversion (ECUD) vs intracorporeal urinary diversion (ICUD). 4 More recently, studies have compared the incidence of long-term complications between ORC and RARC, with a special attention to the development of benign ureteroenteric stricture (UES).…”
Section: Editorial Commentmentioning
confidence: 99%
“…1 As the early learning period for RARC may be more susceptible to stricture complications, the current study highlights the need to maintain established surgical principles to optimize a well-perfused ureteral anastomosis irrespective of the approach. The impact of diversion technique and effect of adjunctive tools such as fluorescence imaging 2 to help minimize ischemia should continue to be prospectively evaluated.…”
Section: Author Replymentioning
confidence: 99%